Proposta de atividades potencialmente interdisciplinares envolvendo noções de análise combinatória e probabilidade - Dias, Reinaldo Amirato (2015)
This is a qualitative study on the interdisciplinary approach to the basics of combinatorics and probability in basic education. It was developed from two basic questions: What are the standards to be met activities considered potentially interdisciplinary? It can develop potentially interdisciplinary activities involving math concepts in the field of combinatorics and probability? We use the concept of interdisciplinarity as one of the ways that articulates the process of teaching and learning, as a way of thinking and acting. It organizes the curriculum and methodological options based teaching and can thus serve as a guiding element in teacher education. We found strong indications in the literature that the teaching notions of probability and combinatorics already in elementary education would be essential to make students enter high school with good sense about data processing, forecasts and combinations. Interdisciplinary activities would be the best ways to give significance to a subject often treated in the abstract, and reduce the average distance between the content taught in the classroom and student daily. The Educational Product, the result of this study consists of six activities involving employment opportunities in various areas relevant to the formation of the individual and applications in everyday situations content. Search address the need for overcoming the fragmented view of the areas of knowledge, in order to recover the integration of knowledge. To expand the potential of interdisciplinary activities apply a workshop involving thirteen teachers who work in different areas. We understand that the use of this product may result in an Educational teaching / learning distanced abstract and mechanical format. Allow space for students to build knowledge, search and dialogue about the concepts involved. These activities also subsidize spaces to interesting debates, with effective participation of students and teachers involved.